Testing, modelling and analysis of full-scale cold-formed steel center-sheathed shear walls in fire. (1st June 2023) - Xing, Yonghui; Zhao, Ou; Wang, Weiyong
Highlights: An innovative CFS shear wall with improved lateral load capacity was proposed and studied. Parametric analysis was conducted to further investigate the fire behavior of the wall. An optimal sheathing thickness was recommended in this paper. Abstract: Cold-formed steel center-sheathed shear wall (CFSCSSW) is an innovative shear wall applied to multi-story cold-formed steel buildings. In this study, six tests were carried out on CFSCSSWs, including one room temperature test to obtain load-bearing capacity and five fire tests to investigate the influence of the vertical load ratio, lateral load ratio, interior stud and aspect ratio on the fire behavior of the CFSCSSWs. Subsequently, finite element models were developed to investigate the influence of various combinations of vertical and lateral loads and the sheathing thickness on the fire behavior of the wall. The research results showed that the temperature distribution along the thickness of the wall section is quite non-uniform and the maximum difference reaches 65% from the hot flange to the cold flange. The effect of the vertical load ratio on the fire resistance of the wall is greater than that of the lateral load ratio. The interior stud plays a positive role in improving the fire resistance of the wall. The aspect ratio has little influence on the fire resistance of the wall. The failure model of the wall mainly depends on vertical or lateral loads as well as the aspect ratio. With the increase in the vertical load ratio, the failure location of the wall moves down. Based on the parametric studies, a sheathing thickness of 0.8 mm was recommended for CFSCSSWs.